A wonderlandiful world - Hale, Shannon (New York : Little, Brown and Co., 2014)
"When a mysterious being from Wonderland begins to infect Ever After High with a strange magic, everything goes topsy-turvy. Lizzie Hearts, Wonderland's future queen; Cedar Wood, daughter of Pinocchio; and Madeline Hatter, heir to the Mad Hatter's Haberdashery & Tea Shoppe, seem to be the only ones who haven't completely lost their heads. It's up to them to save their best friends forever after from a curse that threatens to give their school--and their lives--a very unhappy ending"--Provided by publisher.
5.4
3-6
Keywords: Characters and characteristics in literature -- Juvenile fiction; Friendship -- Juvenile fiction; Boarding schools -- Juvenile fiction; Schools -- Juvenile fiction; Fairy tales; Characters in literature -- Fiction; Friendship -- Fiction; Boarding schools -- Fiction; Schools -- Fiction; Fairy tales; Characters and characteristics in literature -- Fiction; Friendship -- Fiction; Private schools -- Fiction; School stories; Fairy tales; Fairy tales; JUVENILE FICTION / Toys, Dolls, Puppets; JUVENILE FICTION / Fairy Tales & Folklore / General